Validity and reliability of typhoid risk factors questionnaire (TRFQ) in Gombe Metropolis, Gombe State, Nigeria - Tawfiq, Umar Abdullahi; Shohaimi, Shamarina; Mohd Nadzir, Noor Hisham; Nordin, Syafinaz Amin; Ab Rahman, Abdul Hafiz; Salari, Nader (Universiti Putra Malaysia Press, 2022)
Typhoid poses a significant threat to human health, particularly in Africa and Asia, where the disease continues to be endemic. Typhoid caused approximately 8.4 million disability-adjusted life-years worldwide in 2017, with 116,814 deaths. While vaccinations effectively eradicate the endemic infection, limited resources frequently constrained vaccination strategies. Thus, an understanding of the risks associated with typhoid would aid in implementing targeted interventions. In many states of Nigeria, including Gombe, data on typhoid risk factors are unavailable. This study aimed to develop and validate a questionnaire on typhoid risk factors in the Gombe Metropolis. The questionnaire items were based on previously published questionnaires on typhoid and localized typhoid risk factors. After obtaining ethical approval, the drafted instrument was pilot tested among a small population and checked for readability. The questionnaire’s content validity was checked using Fleiss’ Multi-rater kappa, while internal consistency and test-retest reliability were checked using Cronbach’s alpha and intraclass correlation coefficient (ICC), respectively. The questionnaire validation results revealed that the instruments’ readability was easy, content validity with Fleiss’ kappa value of 0.623 was good, internal consistency with Cronbach’s alpha value of 0.720 and McDonald’s omega of 0.703, and test-retest reliability with an ICC estimate of 0.736 was good. The questionnaire was valid and reliable for collecting data on typhoid risk factors in Gombe State, Nigeria, to develop targeted health interventions and guide the Government’s resource prioritization and allocation decisions for efficient disease control.